A world without Islam - Fuller, Graham E. (Little, Brown and Co., 2010)
This book will reshape the way we think about Islam's relationship with the West. What if Islam never existed? To some, it's a comforting thought: no clash of civilizations, no holy wars, no terrorists. Here, political scientist and expert on the Muslim world Graham E. Fuller guides us through history, geopolitics, and religion to investigate whether or not Islam is indeed the cause of some of today's most emotional and important international crises. Fuller takes us from the birth of Islam to the fall of Rome to the rise and collapse of the Ottoman Empire. He examines and analyzes the roots of terrorism, the conflict in Israel, and the role of Islam in supporting and energizing the anti-imperial struggle. Provocatively, he finds that contrary to the claims of many politicians, thinkers, theologians, and soldiers, a world without Islam might not look vastly different from what we know today.--From publisher description